Clinical, economic and humanistic outcomes of medication therapy management services: A systematic review and meta-analysis - Deng, Zhi-Jie; Gui, Lin; Chen, Jing; Peng, Shun-Shun; Ding, Yu-Feng; Wei, An-Hua (Frontiers in Pharmacology, 2023)
Background: Medication therapy management (MTM) services is a method that can effectively improve patients’ conditions, but the efficacy of economic and humanistic outcomes remain unclear. This systematic review and meta-analysis aim to use economic, clinical and humanistic outcomes to evaluate the multi-benefits of MTM services. Method: A systematic review and meta-analysis was conducted by retrieving PubMed, EMBASE, the Cochrane Library and ClinicalTrial.gov from the inception to April 2022. There were two reviewers screening the records, extracting the data, and assessing the quality of studies independently. Results: A total of 81 studies with 60,753 participants were included. MTM services were more effective in clinical outcomes with decreasing the rate of readmission (OR: 0.78; 95% CI: 0.73 to 0.83; I2 = 56%), emergency department visit (OR: 0.88; 95% CI: 0.81 to 0.96; I2 = 32%), adverse drug events (All-cause: OR: 0.68; 95% CI: 0.56 to 0.84; I2 = 61%; SAE: OR: 0.51; 95% CI: 0.33 to 0.79; I2 = 35%) and drug-related problems (MD: −1.37; 95% CI: −2.24 to −0.5; I2 = 95%), reducing the length of stay in hospital (MD: −0.74; 95% CI: −1.37 to −0.13; I2 = 70%), while the economic and humanistic outcomes were less effective. Conclusion: Our systematic review and meta-analysis demonstrated that MTM services had great ability to improve patients’ clinical conditions while the efficacy of economic and humanistic outcomes, with some of the outcomes showing high degree of heterogeneity and possible publication bias, required more future studies to provide stronger evidence. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=349050], identifier [CRD42022349050].